Psychologiczne aspekty zakończenia czynnego uprawiania sportu - Konrad Kraszewski; Anna Kraszewska (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2016)
Age and injury may be the reasons of the sport career termination. Depression and prolonged stress are also factors of termination. After finishing the sport’s career, sportsmen’ life depends on cultural aspects, education and preparations to other type of activity. Psychological aid may be very helpful.